Implementasi Konsep Internet of Things pada Sistem Monitoring Banjir menggunakan Protokol MQTT - Chrisyantar Hasiholan; Rakhmadhany Primananda; Kasyful Amron (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
In general, Internet of Things can be interpreted as connecting various objects around with an internet network. To implement it, the Internet of Things requires a communication path to suit the needs of the system. One protocol that suits the application of the concept of Internet of Things is the Message Queue Telemetry Transport (MQTT) protocol. The MQTT protocol is often used in systems that use the concept of the Internet of Things, one of which is the monitoring system. One aspect of life that requires a monitoring system is a natural disaster. From various natural disasters that occurs Indonesia, Flood is a natural disaster that quite often hit many cities in Indonesia. Therefore, this research implements the concept of Internet of Things on flood monitoring system using MQTT protocol. Based on test results, it is concluded that MQTT protocol can be used in flood monitoring system. The accuracy of the system is 97.801% with obtained standard deviation is Â± 0.0309 cm. In scalability testing, obtained the average percentage of success rate of 100%, 99.87% and 99.93% on thread trials 100, 250 and 500, which each performed 3 times. And on data integrity testing, the MQTT protocol obtains the same 100% data in each experiment with intervals of 10ms, 100ms and 1000ms.